Non-Secretor Status Due to FUT2 Stop Mutation Is Associated with Reduced Rotavirus Infections but Not with Other Enteric Pathogens in Rwandan Children - Jean Bosco Munyemana; Jean Claude Kabayiza; Eric Seruyange; Staffan Nilsson; Gustaf E. Rydell; Anna Martner; Maria E. Andersson; Magnus Lindh (Microorganisms)
Enteric pathogens remain a health threat for children in low-income countries. A single nucleotide polymorphism (SNP) in the FUT2 gene that precludes the expression of fucosyltransferase 2 has been reported to influence the susceptibility to rotavirus and norovirus infections. The aim of this study was to investigate the association between G428A at rs601338 (stop codon variant) in the FUT2 gene and a range of enteric pathogens in children under 5 years of age. Rectal swab samples from 668 children (median age 13.6 months, 51% males, 93% rotavirus vaccinated, 468 with diarrhea) from Rwanda were analyzed via PCR for pathogen detection and SNP genotyping. A FUT2 stop codon (‘non-secretor’ status) was found in 19% of all children. Rotavirus was detected in 5.3% of non-secretors compared with in 13% of secretors (OR = 0.39, p = 0.019). Rotavirus P[8] was the predominant genotype and was found in 2.3% of non-secretors compared with 8.8% of secretors (p = 0.009). There was no association with any other pathogen, including noroviruses, of which 2 of 14 GII.4 infections were detected among non-secretors. Thus, the FUT2 stop codon variant was associated with rotavirus but not with any other pathogen.